2010
DOI: 10.1124/jpet.109.161661
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of l-Cysteine in Isolated Whole-Bladder Preparations from Neonatal and Adult Rats

Abstract: The present study was undertaken to compare the effects of the thiol reagents L-cysteine and (diazene dicarboxylic acid bis 5N,N-dimethylamide) diamide on contractile activity of neonatal and adult rat bladders. In vitro whole-bladder preparations from Wistar rats were used to study the modulation of spontaneous bladder contractions by thiol reagents. After blocking cholinergic and adrenergic transmission with atropine and guanethidine, L-cysteine facilitated spontaneous bladder contractions in neonatal rat bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Taken together, these findings suggest that L-cysteine elicits contraction of PulmDA rings by promoting Ca 2ϩ influx via nifedipinesensitive Ca 2ϩ channels and intracellular Ca 2ϩ release from the sarcoendoplasmic reticulum. Our results are consistent with the data obtained in both smooth and striated muscle, which indicate that L-cysteine is an important modulator of Ca 2ϩ homeostasis (13,21,54). We also observed that neither the CSE inhibitor PPG nor the CBS inhibitor AOA significantly affected L-cysteine-induced contraction of PulmDA rings.…”
Section: Discussionsupporting
confidence: 95%
“…Taken together, these findings suggest that L-cysteine elicits contraction of PulmDA rings by promoting Ca 2ϩ influx via nifedipinesensitive Ca 2ϩ channels and intracellular Ca 2ϩ release from the sarcoendoplasmic reticulum. Our results are consistent with the data obtained in both smooth and striated muscle, which indicate that L-cysteine is an important modulator of Ca 2ϩ homeostasis (13,21,54). We also observed that neither the CSE inhibitor PPG nor the CBS inhibitor AOA significantly affected L-cysteine-induced contraction of PulmDA rings.…”
Section: Discussionsupporting
confidence: 95%
“…Thus, to interpret findings from small isolated preparations requires them to be validated with whole organ preparations. To date most of this work has used bladders from small rodents maintained in physiological saline environments (Drake et al, 2003a ; Gillespie et al, 2003 ; Fabiyi and Brading, 2006 ; Buyuknacar et al, 2010 ). Extrapolating findings generated using small laboratory animals to the physiology of urine storage and voiding in large animals and the clinical context is difficult, and requires validation as additional issues have to be reconciled such as: differences in the base-line physiological properties of larger bladders and experimental considerations (adequate tissue perfusion and environmental control).…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacology of the rat urinary bladder also changes during postnatal development. For example, the neonatal rat bladder (10–21 days) is very sensitive to the inhibitory effect of nitric oxide5 and the excitatory effect of L ‐cysteine 6. These effects appear to be markedly diminished during postnatal development as they have not been detected in bladders from adult rats 6–8.…”
Section: Introductionmentioning
confidence: 99%